A reliability assessment of the basic erosive wear examination and the tooth wear evaluation system 2.0 utilizing intraoral scan data - Maria Lorens; Iwona Tomaszewska (PLoS ONE, 2026)
Objectives This study assessed the reliability and clinical applicability of two tooth wear screening indices—Basic Erosive Wear Examination (BEWE) and the Tooth Wear Screening module of the Tooth Wear Evaluation System 2.0 (TWES 2.0)—using intraoral scans. Materials and methods A total of 246 anonymized intraoral scans from adult patients were independently evaluated by two calibrated examiners. Examiner calibration was performed prior to the study using a representative set of intraoral scans. Calibration was repeated until consensus regarding the application of the scoring criteria was achieved before formal data collection. Scores for all sextants were recorded for BEWE and TWES 2.0. Inter-rater agreement was primarily assessed using weighted kappa coefficients, as BEWE and TWES 2.0 are ordinal, numerically coded indices. Wilcoxon signed-rank tests were additionally used to assess systematic directional differences between paired scores. Statistical significance was set at p < 0.05. Results BEWE demonstrated good reliability, with weighted kappa values ranging from 0.760 to 0.851 across sextants, 0.868 for the total BEWE score, and an overall weighted kappa of 0.841. TWES 2.0 showed moderate to good reliability, with weighted kappa values ranging from 0.543 to 0.761 across sextants and an overall weighted kappa of 0.715. Conclusions Both BEWE and TWES 2.0 are reliable and practical for screening noncarious tooth wear via intraoral scans. BEWE showed slightly higher inter-rater consistency, whereas TWES 2.0 allows more detailed evaluation of occlusal and palatal surfaces. These indices can support standardized monitoring, early detection, and clinical management of tooth wear. Examiner calibration remains essential, particularly for TWES 2.0. Clinical trial registration This was a retrospective reliability study and did not involve an interventional clinical trial; therefore, registration was not applicable.